Prenatal development of brain in goats - Lucy K M (Department of Anatomy, College of Veterinary and Animal Sciences, 2005)
Studies on the prenatal development of brain in goats were conducted using 52 foetuses of varying gestational ages ranging from 24 days of gestation (1.4cm CRL) to full term (41.5cm CRL). The project was undertaken to trace the developmental pattern of brain and its relationship with age, body weight, cranial size and other body parameters. After recording the body measurements and craniometry, the material was fixed in 10 percent neutral buffered formalin. Then the encephalometry was recorded and standard procedures were adopted for histoarchitectural and histochemical studies. At 24 days, dilated cephalic end of the neural tube showed the five brain vesicles, viz., telencephalon, diencephalon, mesencephalon, metencephalon and myelencephalon. Histologically, wall of the neural tube showed an inner ependymal, middle mantle and outer marginal layers bounded by the inner and outer limiting membranes. The thickest inner ependymal layer was composed of proliferating neuroepithelial cells that gave rise to the neuroblasts and spongioblasts. All the head parameters showed a greater increase during early gestation but the encephalometric parameters showed a spurt in growth during terminal stages which explains the highly convoluted pattern of cerebral and cerebellar cortices. Cephalic region of head grew faster than the face. Cartilaginous cranial vault developed by 40 days and boundaries of skull bones could be identified by 54 days. A highly significant positive correlation existed among brain length and medial length of frontal and parietal bones. Among the body parameters, maximum correlation was noticed between the body weight and brain weight and also between the brain weight and total body length. Regression equations were derived from significantly correlated brain and body parameters that could be used to predict brain parameters during gestation from known body parameters of the foetus. Thus one can assess the normal growth rate of brain and cases of hypoplasia and other disorders. Contributions of cerebral hemispheres and cerebellum to the total brain weight showed a sharp and steady increase indicating a gradual “cephalic shift” of function from phylogenetically older brainstem to the higher cerebral and cerebellar cortices. Right cerebral hemisphere was slightly heavier (0.88 percent) than the left one. During second month, surface of the cerebral hemisphere was almost smooth. By 69 days, gyri and sulci started developing and at the beginning of fifth month, most of them appeared. By term, the cerebral surface attained adult pattern. Histologically, towards the middle of second month, neuroblasts and spongioblasts of the inner ependymal layer of the cerebral wall migrated outwards giving rise to a superficial gray cortex. By 76 days, the cortex revealed four layers, viz., outer molecular, superficial granular, intermediate granular and deep granular layers. Cortical migration came to an end by about 12 weeks of gestation and the cells were undergoing differentiation during the fourth month. During the fifth month, the neocortex was divided into six layers. Cortex was thicker at the top of the gyrus and the mean thickness decreased from fourth to fifth month leading to a better vascularisation of the cortical tissue by the pial vessels. Hippocampus appeared at 48 days and was well developed towards term. Basal nuclei started developing by 40 days and all the components developed as a distinct entity towards term. Cerebellum developed from rhombic lips of the roof of the metencephalon and formed the midline vermis and two lateral hemispheres by 48 days. Folia started developing at 62 days and by 101 days of age, six lobules were identified. By 124 days, all the nine classical lobules appeared. During the seventh week, the external granular layer unique to the foetal cerebellum appeared. Neurons of the deep cerebellar nuclei were visible by 48 days. Primitive Purkinje cells, the internal granular layer and the white matter started differentiating towards the end of second month. All the layers were well developed during the fifth month and the external granular layer became very thin by term indicating the functional maturity. Cellular aggregations, the nuclei, first appeared in diencephalon during seventh week. Pineal body, optic chiasma, infundibulum and subcommissural organ developed during the same period. Mesencephalon showed tectum, tegmentum and crura cerebri by 48 days. Reticular formation of the tegmentum and multipolar neurons of the red nucleus appeared during seventh week. Basal plate of metencephalon developed into the pons, which showed motor nuclei of origin for cranial nerves V, VI and VII and the pontine nuclei at 48 days. During fifth month, pons was divided into tegmental and basilar parts. By 40 days of gestation, the roof plate of rhombencephalon expanded enormously and as a result the entire alar and basal plates were displaced laterally and ventrally. The main difference of the medulla oblongata from the spinal cord was that a sharp demarcation between the gray and white substances disappeared in this region. Nuclei appeared at 48 days and nerve fibres crossing in different directions broke up the gray substance into a mixture of gray and white known as the reticular formation. The dilated cavities of the brain vesicles were the forerunners of the ventricular system. Lateral ventricles appeared as a distinct entity by 27 days and extended into lobes of cerebral hemispheres at 48 days. The roof of third ventricle was triangular and wide. The three recesses of third ventricle were evident from the second month. Cavity of hindbrain expanded to the sides to form the fourth ventricle at 40 days and communicated with the subarachnoid space by the foramina of Luschka. Choroid plexus first appeared in brain ventricles at 40 days. Primitive neurons could be clearly distinguished from spongioblasts at 40 days. Nissl granules appeared in some neurons by the middle of fourth month and towards term, most neurons showed Nissl granules. Astrocytes and oligodendrocytes started differentiating by 58 days but the microglia appeared at 76 days. Ependyma developed cilia on their luminal surface in the second month. Pia mater started differentiating by 24 days, dura by 40 days and the arachnoid by 48 days of age. Histochemical studies revealed that the myelination began in the foetal brain during third month. In the fifth month, most of the fibres were myelinated. Glycogen could be demonstrated in the neurons, ependyma, astrocytes and choroid plexus epithelium. Alkaline phosphtase reaction was noticed in the outer plexiform layer of cerebral cortex, white matter, hypothalamus, blood vessels, choroid plexus, pia-arachnoid and ependyma. In general, acid phosphatase activity was less pronounced in the foetal brain.